Towards New Oligomesogenic Phosphonic Acids as Stabilizers of Nanoparticles Colloids in Nematic Liquid Crystals - Prodanov, Maksym F.; Diakov, Maksym Y.; Vlasenko, Ganna S.; Vashchenko, Valerii V. (Synlett, 2015)
Several synthetic strategies for the construction of linear and branched oligomesogenic phosphonic acids are examined, which differ in the method of building the key bimesogen unit. An efficient synthetic approach to the most promising compounds employs regioselective Kumada cross-coupling between [11-(4′-pentylbiphenyl-4-yl)undecyl]magnesium bromide and 4-(11-bromoundecyl)-4′-iodobiphenyl as the key step. Preliminary studies on the ability of the new ligands to stabilize nanoparticles colloids in nematic liquid crystals are undertaken for the example of quantum dots.
Keywords: acylation; cross-coupling; phosphonic acids; total synthesis; ligands